Pelatihan Pemanfaatan Affiliate Marketing Sebagai Peluang Bisnis Bagi Pemuda AMGPM Ranting XIV Cabang Bethel Di Kota Ambon - Anna Valensia Christianty de Fretes; Feky Reken; Siska Jeanete Saununu; Nurul Maghfirah; Felix Chandra (Jurnal Pengabdian kepada Masyarakat Nusantara, 2023)
This service aims to assist Youth Branch XIV Cabang Bethel in carrying out the Science and Technology Work Program which is beneficial for the development of member start-up businesses as well as providing motivation and innovation that can be used as a Business Opportunity for youth in general. Ranting XIV of the Cabang Bethel consists of 50 Branch Members including 15 administrators and 4 Trustees. The existing Science and Technology Work Program at the Branch requires the Branch to make a new breakthrough that is useful for the existing and not yet existing Startup Businesses. On the other side, the average AMGPM Ranting XIV Bethel youth member has a Tiktok account but does not understand the use and benefits of affiliate marketing in this application. Of the 35 participants who attended, 10 of them had pilot businesses in the form of goods and services. However, in its development it has not yet achieved the desired profit, so development for the sake of development is needed. The method used in this activity is in the form of lectures, discussions, questions and answers and the practice of becoming a Tiktok affiliate. The training begins with the theory and practice of affiliate registration on the Tiktok application and how to publish content for sale. This training tends to invite participants to market products without production costs. Based on the results of the evaluation, the TIM found that: 1) Participants were motivated to take advantage of affiliate marketing on the TikTok application to develop businesses, as well as start new businesses. This can be seen from the number of participants who registered accounts to become Tiktok application affiliators, as many as 23 of the 35 participants who attended, using Smartphones and Laptops assisted by TIM. 2) This training helps realize the Bethel Branch XIV Science and Technology Work Program which is beneficial to its members.